20/(fasting C-peptide × fasting plasma glucose) is a simple and effective index of insulin resistance in patients with type 2 diabetes mellitus: a preliminary report - Ohkura, Tsuyoshi (BioMed Central, 2013)
BACKGROUND: We developed a simple and new insulin resistance index derived from a glucose clamp and a meal tolerance test (MTT) in Japanese patients with type 2 diabetes mellitus. METHODS: Fifteen patients [mean age: 53 years, fasting plasma glucose (FPG) 7.7 mmol/L, HbA1c 7.1% (54 mmol/mol), body mass index 26.8 kg/m(2)] underwent a MTT and a glucose clamp. Participants were given a test meal (450 kcal). Plasma glucose and insulin were measured at 0 (fasting), 30, 60, 120, and 180 min. Serum C-peptide immunoreactivity (CPR) was measured at 0 (fasting; F-CPR) and 120 min. Homeostasis model assessment of insulin resistance (HOMA-IR) and insulin sensitivity indices (ISI) were calculated from the MTT results. The glucose infusion rate (GIR) was measured during hyperinsulinemic–euglycemic glucose clamps. RESULTS: The mean GIR in all patients was 5.8 mg·kg(–1)·min(–1). The index 20/(F-CPR × FPG) was correlated strongly with GIR (r = 0.83, P < 0.0005). HOMA-IR (r = −0.74, P < 0.005) and ISI (r = 0.66, P < 0.01) were also correlated with GIR. In 10 patients with mild insulin resistance (GIR 5.0–10.0 mg·kg(–1)·min(–1)), 20/(F-CPR × FPG) was very strongly correlated with GIR (r = 0.90, P < 0.0005), but not with HOMA-IR and ISI (r = −0.49, P = 0.15; r = 0.20, P = 0.56, respectively). In patients with mild insulin resistance, plasma adiponectin (r = 0.65, P < 0.05), but not BMI or waist circumstance, was correlated with GIR. CONCLUSIONS: 20/(F-CPR × FPG) is a simple and effective index of insulin resistance, and performs better than HOMA-IR and ISI in Japanese patients with type 2 diabetes mellitus. Our results suggest that 20/(F-CPR × FPG) is a more effective index than HOMA-IR in Japanese patients with mild insulin resistance.